Case in collective bargaining & industrial relation : - Dilts, David A. (McGraw-Hill/Irwin, 2007)
Cases in Collective Bargaining and Industrial Relations contains 81 cases that vary in length, complexity and numbers of issues. A major objective of the book is to provide a means by which students can apply principles, concepts, and legal considerations to actual decision situations and confrontations between labor and management. These cases have been tested in seminars and classes, and are challenging, fascinating learning instruments. As in previous editions, the cases are divided into two parts. Part One presents National Labor Relations Board cases as restructured from published reports of the NLRB and court decisions. Part Two consists of cases adapted from grievance-arbitration decisions.